Hubungan Perilaku Dengan Konsep Diri Pada Pasien Chronic Kidney Diseases Yang Menjalani Hemodialisa Diruang Hemodialisa RSUD Dr. Moewardi - Prasetyo Agung Nugroho (Poltekkes Kemenkes Surakarta, 2018)
Background. Chronic Kidney Diseases (CKD) is a progressive deviation of kidney, the kidneys are unable to function to maintain metabolic balance , so as to resolve the issue carried out various therapies one of which is dialysis or Hemodialysis (HD). CKD patients undergoing hemodialysis will experience physical and psychosocial problems that affect the behavior and self-concept. This research is to know the Relationship Between Behavior And Self-concept in patients at Chronic Kidney Diseases That Undergoing Hemodialysis In Hemodialysis Unit of Hospital Dr. Moewardi. Methods. This type of research is correlational with the design of cross sectional and analysis the data used is the test Product Moment Pearson. Research Result. The results of this research is there is a relationship between the behavior and self-concept of patients undergoing hemodialysis in Hemodialysis Unit of Hospital Dr. Moewardi. This is evidenced by Pearson Product Moment analysis test which obtained significance value (p value) 0,000 < 0,05 (α = 5 %). Conclusion. Behaviors related to self-concept in patients with CKD undergoing Hemodialysis.